SARS-CoV-2 neutralizing antibody response after three doses of mRNA1273 vaccine and COVID-19 in hemodialysis patients - Wang, Xiaoling; Han, Maggie; Fuentes, Lemuel Rivera; Thwin, Ohnmar; Grobe, Nadja; Wang, Kevin; Wang, Yuedong; Kotanko, Peter (Frontiers in Nephrology, 2022)
Background In hemodialysis patients, a third vaccination is frequently administered to augment protection against COVID-19. However, newly emerged B.1.1.159 (Omicron) variant may evade vaccinal protection more easily than previous strains. It is of clinical interest to better understand the neutralizing activity against SARS-CoV-2 variants after booster vaccine or COVID-19 infection in these mostly immunocompromised patients. Methods Hemodialysis patients from four dialysis centers were recruited between June 2021 and February 2022. Each patient provided a median of six serum samples. SARS-CoV-2 neutralizing antibodies (nAb) against Wild Type (WT) or Omicron were measured using the GenScript SARS-CoV-2 Surrogate Virus Neutralization Test Kit. Results Forty-two patients had three doses of mRNA1273. Compared to levels prior to the 3rd dose, nAb-WT increased 18-fold (peak day 23) and nAb-Omicron increased 23-fold (peak day 24) after the 3rd dose. Peak nAb-WT exceeded peak nAb-Omicron 27-fold. Twenty-one patients had COVID-19 between December 24th, 2021, and February 2nd, 2022. Following COVID-19, nAb-WT and nAb-Omicron increased 12- and 40-fold, respectively. While levels of vaccinal and post-COVID-nAb-WT were comparable, post-COVID-nAb-Omicron levels were 3.2 higher than the respective peak vaccinal nAb-Omicron. Four immunocompromised patients having reasons other than end stage kidney disease have very low to none nAb after 3rd dose or COVID-19. Conclusions Our results suggest that most hemodialysis patients have a strong humoral response to the third doses of vaccination, and an even stronger post-COVID-19 humoral response. Nevertheless, neutralizing antibody levels clearly decay over time. These findings may inform ongoing discussions regarding a 4th vaccination in hemodialysis patients.